El Internacionalización y Comercio Electrónico de los agroexportadores de Lima - Perú en el año 2023 - Flores Condori, Yeon (2025)
In 2019, global e-commerce grew significantly, representing 30% of world GDP and playing a crucial role in times of crisis by facilitating internationalization and increasing competition, benefiting MSMEs. In Latin American countries, although it continues to grow, it is warned that non-digitized SMEs could lose up to 20% in sales. In Peru, e-commerce experienced growth in 2020 but faced barriers, motivating companies to expand international shipments. The objective of the study was to determine the relationship between internationalization and e-commerce in agro-exporting companies in Lima, Peru, by 2023. A quantitative method with a correlational approach and a non-experimental cross-sectional design was used. The population consisted of 1626 agro-exporting companies, and the sample included 70 collaborators from the commercial department, selected by convenience sampling. Surveys were conducted with specific questionnaires, carefully analyzed and compiled to ensure the validity and reliability of the data, using SPSS software for validation. The results showed a high correlation of 0.807 between the variables and a significance level of 0.001 accepting H1 and rejecting H0. Keywords: E-commerce, Internationalization, Agro-exporters, Logistics